Support for Conciliatory Policies in the Israeli-Palestinian Conflict: The Role of Different Modes of Identification and Territorial Ownership Perceptions - Storz, Nora; Martinović, Borja; Rosler, Nimrod (Frontiers in Psychology, 2022)
Understanding people’s attitudes toward conciliatory policies in territorial interethnic conflicts is important for a peaceful conflict resolution. We argue that ingroup identification in combination with the largely understudied territorial ownership perceptions can help us explain attitudes toward conciliatory policies. We consider two different aspects of ingroup identification—attachment to one’s ethnic ingroup as well as ingroup superiority. Furthermore, we suggest that perceptions of ingroup and outgroup ownership of the territory can serve as important mechanisms that link the different forms of ingroup identification with conciliatory policies. In the context of the Israeli-Palestinian conflict, among Israeli Jews (N = 1,268), we found that ingroup superiority, but not attachment, was negatively related to conciliatory policies. This relationship was explained by lower outgroup (but not by higher ingroup) ownership perceptions of the territory. Our findings highlight the relevance of studying ingroup superiority as a particularly relevant dimension of identification that represents a barrier to acknowledging outgroup’s territorial ownership, and is thus indirectly related to less support for conciliatory policies in intergroup conflict settings.